Antimicrobial activities of gynura procumbens leaves extract against selected bacteria / Liliwirianis Nawi ...[et al.] - Nawi, Liliwirianis; Md Isa, Nurun Nadhirah; Musa, Nor Lailatul Wahidah; Mohd Jan, Sarah Laila; Shaikh Nasir, Nur Thabitah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Gynura procumbens or Sambung Nyawa is a tropical plants species from the Asteraceae family. The objectives of this study were to determine antimicrobial activity and Minimal Inhibition Concentration (MIC) of G. procumbens leaf extracts against selective Gram-positive and Gramnegative bacteria. Methanol and hexane were the two extraction solvents that had been used. Four concentrations of extracts; 50 mg/mL, 100 mg/mL, 200 mg/mL, and 400 mg/mL were prepared for antimicrobial activity. Meanwhile for MIC determination, 6.25 mg/mL, 12.5 mg/mL, 25 mg/mL and 50 mg/mL concentrations were prepared. By using disc diffusion method, the methanol extract of G. procumbens leaves showed antimicrobial activities against Staphylococcus aureus, Bacillus subtilis, Klebsiella pneumoniae, and Pseudomonas aeruginosa compared to hexane extract. Highest antimicrobial activities were recorded against S. aureus at 400 mg/mL concentrations with 10.5 mm of inhibition zone. Broth dilution assay resulted MIC for methanol crude extract against S. aureus, B. subtilis, K. pneumoniae, and P. aeruginosa were at 12.5 mg/mL, 25 mg/mL, and 50 mg/mL, respectively